A new topology for nonisolated multiport zero voltage switching dc‐dc converter. (22nd February 2018) - Babaei, Ebrahim; Saadatizadeh, Zahra; Chavoshipour Heris, Pedram
Summary: In this paper, a new multiport zero voltage switching dc‐dc converter is proposed. Multiport dc‐dc converters are widely applicable in hybrid energy generating systems to provide substantial power to sensitive loads. The proposed topology can operate in 3 operational modes of boost, buck, and buck‐boost. Moreover, it has zero voltage switching operation for all switches and has the ability to eliminate the input current ripple; also, at low voltage side, the input sources can be extended. In addition, it has the ability of interfacing 3 different voltages only by using 3 switches. In this paper, the proposed topology is analyzed theoretically for all operating modes; besides, the voltage and current equations of all components are calculated. Furthermore, the required soft switching and zero input currents ripple conditions are analyzed. Finally, to demonstrate the accurate performance of the proposed converter, the Power System Computer Aided Design(PSCAD)/Electro Magnetic Transient Design and Control(EMTDC) simulation and experimental results are extracted and presented. Abstract : In this paper, a new multiport zero voltage switching dc‐dc converter with cancelling the input current ripple and extending the input sources at low voltage side is proposed. The proposed topology can operate in 3 operational modes of boost, buck, and buck‐boost. In addition, it has the ability of interfacing 3 different voltages only by using 3 switches.